2007
DOI: 10.1097/01.tp.0000248759.37146.3d
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic Kidney Disease Is a Risk Factor for New-Onset Diabetes After Transplantation

Abstract: We conclude that ADPKD is a significant risk factor for the development of NODAT. This may influence the follow up and management choices of these patients in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 16 publications
1
45
1
4
Order By: Relevance
“…18,19 However, corticosteroids, with their dose-dependent effect to stimulate insulin resistance, are associated with the highest risk of PTDM. 19,20 The drug regimen administered to both study groups was comparable, including steroid administration, therefore it seems that medication factor did not influenced the study results. The present study revealed a significant association between PTDM and CAPN10 gene SNP-63 (rs5030952:C4T) polymorphism, as well as 1-1-2 haplotype (derived from SNP-43 (rs3792267), SNP-19 (rs3842570) and SNP-63 (rs5030952)).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, corticosteroids, with their dose-dependent effect to stimulate insulin resistance, are associated with the highest risk of PTDM. 19,20 The drug regimen administered to both study groups was comparable, including steroid administration, therefore it seems that medication factor did not influenced the study results. The present study revealed a significant association between PTDM and CAPN10 gene SNP-63 (rs5030952:C4T) polymorphism, as well as 1-1-2 haplotype (derived from SNP-43 (rs3792267), SNP-19 (rs3842570) and SNP-63 (rs5030952)).…”
Section: Discussionmentioning
confidence: 99%
“…17 However, several other risk factors such as age, pre-transplant weight, certain infections and genetic predisposition have also been identified or suggested. [18][19][20][21][22][23] To the best of our knowledge, the role of hyperparathyroidism in developing NODAT has not been studied. This association could have important implications in the assessment of the individual patient risk of NODAT and in how to handle hyperparathyroidism in transplanted patients.…”
Section: Introductionmentioning
confidence: 99%
“…15 However a threefold increased risk of developing new-onset diabetes after transplantation in ADPKD has recently been reported. 19 …”
Section: Chronic Kidney Disease and Renal Replacement Therapymentioning
confidence: 99%